(3aVGAGJ GdHjGfGJ GdVNeI (B:s (3GdEHMGQ ddMOhO ZjQ GdeMOhOI (B= Big data spaces : sailing for umlimted limits /s - (3SGde, aGWeI SYjOs; (3GdXghQj, YHO eQRhbs ((3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3eOGO ddfTQ hGdJhRjY,s, 2020)
(3jJfGhd cJGH (B((3aVGAGJ GdHjGfGJ GdVNeI GdEHMGQ ddMOhO ZjQ GdeMOhOI(B) (3hGdPj bGe HJCdjag (B((3aGWeI SYjO SGde hYHO eQRhb GdXghQj(B) (3aj MhGdj (B(275) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdHjGfGJ GdVNeI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3eaghe GdHjGfGJ GdVNeI, ef GdHjGfGJ GdVNeI Edi GdHjGfGJ GdPcjI, GdHjGfGJ GdVNeI aj GdeLGdGJ GdeNJdaI, JbfjGJ GdHjGfGJ GdVNeI heUGOQgG, feGPL ef JWHjbGJ GdHjGfGJ GdVNeI(B.s
(3ENQGL GdcJGH hJUeje GdZdGa (B: (3aGWeI SYjO SGde, TeG SdWGf Bd Ydj(B.s
(3HHdjhLQGajI (B: (3UaMI (B272-275.s
Keywords: (3GdHjGfGJ GdVNeIs; (3EOGQI GdeYdheGJs -- (3eYGdLI HjGfGJs